DEVELOPMENT OF SELF-EDUCATIONAL COMPETENCE OF HIGHER EDUCATION STUDENTS (Innovative professional education, 2022)
The theses define the factors and pedagogical conditions for the development of self-educational competence of students of higher education by means of expert evaluation (targeted development of students' need for self-education and self-improvement; systematic and consistent formation of "learning ability" in students of higher education; creation of a favorable information and educational environment for self-educational activities of students ; the technology of organizing self-education and self-education of higher education seekers, the purpose of the researched process is determined.
Keywords: self-educational competence, pedagogical conditions, factors, student, higher education student